Artificial Intelligence for internet of things design principle, modernization, and techniques - Thillaiarasu, N; Tripathi, Suman Lata; Dhinakaran, V (CRC Press, 2023)
"The text comprehensively discusses design principles, modernization techniques, advanced developments in artificial intelligence. The text will be helpful for senior undergraduate, graduate students, and academic researchers in diverse engineering fields including electrical, electronics and communication, and computer"--...